Manajemen strategi melalui analisis SWOT dan TOWS dalam Upaya Pengembangan Lembaga Pendidikan (Studi kasus di lembaga pendidikan islam) - Fithroh, Indah Nur Af’idatun; Suklani, Suklani (Jurnal Ilmiah Wahana Pendidikan, 2024)
In this dynamic environmental situation, educational management must be able to create an organization that can provide services that satisfy society in general and educational objects (students and parents) in particular. Therefore, in the process of implementing educational activities, decisions and steps are needed to be taken to make education better, which is called strategic management. Based on this explanation, this research aims to explore and analyze strategic management through SWOT and TOWS analysis in efforts to develop Islamic educational institutions. Then, the research method interpreted in this research is a case study with a qualitative approach. The data collection method applied in this research was interviews and questionnaires given to education staff and educators at the MDTA. Furthermore, the results of the TOWS and SWOT analysis obtained in the research show that the strategy pattern that should be used by the Islamic educational institution, MDTA Al-Barokah, is an aggressive strategy pattern which is supported by the value of the SWOT analysis results showing a positive difference on each axis line, namely the x axis. = 1.12 and y-axis= 0.56.